2020
DOI: 10.1515/hf-2020-0182
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of wood with atmospheric plasma discharge: study of the treatment process, dynamic wettability and interactions with a waterborne coating

Abstract: Plasma treatment is becoming a mature technique for modification of surfaces of various materials, including wood. A better insight in the treatment process and the impact of the plasma on properties of wood bulk are still needed. The study was performed on Norway spruce and common beech wood, as well as their thermally modified variations. The formations of the airborne discharge, as well as mass changes of the treated wood, were monitored. The impact of such treatment on wood-coating interaction was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…It has also been found in the literature that the plasma modification process changes the adhesion strength and the parameters of the plasma treatment process have an effect on the adhesion strength, and this is similar to the results of the present study. [ 48 , 50 , 51 , 53 , 64 , 65 ]. In addition, it has been found in the literature that the conditions of heat treatment are also effective on the adhesion strength and this is similar to the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found in the literature that the plasma modification process changes the adhesion strength and the parameters of the plasma treatment process have an effect on the adhesion strength, and this is similar to the results of the present study. [ 48 , 50 , 51 , 53 , 64 , 65 ]. In addition, it has been found in the literature that the conditions of heat treatment are also effective on the adhesion strength and this is similar to the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting use of plasmas in wood surface modification is to oxidize its polymeric constituents to increase its surface free energy and wettability. Over the last 5 years, many workers explored this application to increase the interactions between wood and adhesives or coatings [176][177][178][179][180][181][182][183][184][185][186][187]. They found that using reactive carrier gases such as air and O 2 would lead to the creation of polar groups such as carboxyl and carbonyl at the surface of the treated wood, increasing its hydrophilicity and surface free energy.…”
Section: Plasma Modificationmentioning
confidence: 99%
“…While plasma treatments require expensive equipment [20], they are quite scalable and allow for the preparation of durable coatings. Over the last five years, many authors studied the utilization of non-thermal plasma treatments to increase the surface free energy of wood with the objective to improve its wettability and the penetration of coatings [177,180,181,186,188,189]. Haase et al found that pre-treating black spruce with a glow-discharge plasma would improve the penetration of coatings without increasing their adhesion [176].…”
Section: Economical Aspectsmentioning
confidence: 99%
“…Many studies have shown that plasma treatment of the wood surface significantly increased the reactive groups. These groups would accelerate polymerization of ESO. In the literature, dielectric barrier discharge (DBD) and other low-temperature plasmas have been used to modify the wood surface. In this work, gliding arc discharge (GAD) plasma, which was found previously to be very efficient in initiating oxidation and degradation of organic compounds, was employed for the first time to modify the wood surface.…”
Section: Introductionmentioning
confidence: 99%